Relação de troca entre eficiência energética e eficiência espectral em redes de comunicação sem fio com múltiplas antenas - Rayel, Ohara Kerusauskas (2015)
In this dissertation, we investigate the Energy Efficiency-Spectral Efficiency (EE-SE) trade- off of a multiple antenna wireless communication system employing Transmit Antenna Selection/Maximum Ratio Combining (TAS) scheme. A realistic power consumption model (PCM) is considered, and it is shown that the use of TAS/MRC can provide significant energy savings when compared to Multiple-Input Multiple-Output (MIMO) in the low to medium spectral efficiency region, regardless the number of antennas, as well as outperform transmit beamforming scheme (MRT) for the entire spectral efficiency range. For a fixed number of receive antennas, our results also show that the energy efficiency gain of TAS over MIMO becomes even greater as the number of transmit antennas increases. The optimal value of spectral efficiency that maximizes the energy efficiency is obtained analytically, and confirmed by numerical results. Expressions that evaluate the capacity and the EE-SE trade-off for TAS under the influence of receiver correlation are obtained and it is shown that considering a non- realistic power consumption model can lead to mistakes when comparing TAS and MIMO.